Dynamics of Human Mitochondrial Complex I Assembly: Implications for Neurodegenerative Diseases - Giachin, Gabriele; Bouverot, Romain; Acajjaoui, Samira; Pantalone, Serena; Soler-López, Montserrat (Frontiers in Molecular Biosciences, 2016)
Neurons are extremely energy demanding cells and highly dependent on the mitochondrial oxidative phosphorylation (OXPHOS) system. Mitochondria generate the energetic potential via the respiratory complexes I to IV, which constitute the electron transport chain (ETC), together with complex V. These redox reactions release energy in the form of ATP and also generate reactive oxygen species (ROS) that are involved in cell signaling but can eventually lead to oxidative stress. Complex I (CI or NADH:ubiquinone oxidoreductase) is the largest ETC enzyme, containing 44 subunits and the main contributor to ROS production. In recent years, the structure of the CI has become available and has provided new insights into CI assembly. A number of chaperones have been identified in the assembly and stability of the mature holo-CI, although they are not part of its final structure. Interestingly, CI dysfunction is the most common OXPHOS disorder in humans and defects in the CI assembly process are often observed. However, the dynamic of the events leading to CI biogenesis remains elusive, which precludes our understanding of how ETC malfunctioning affects neuronal integrity. Here, we review the current knowledge of the structural features of CI and its assembly factors and the potential role of CI misassembly in human disorders such as Complex I Deficiencies or Alzheimer’s and Parkinson’s diseases.